Development and initial validation of the Multidimensional Empathy Scale for Adolescents - Jung, Sujong; Kim, Eunha (Asian Journal of Social Psychology, 2023)
Adolescence is a transitional phase in psychosocial development in which individuals learn to navigate their social worlds. The need to socialize, connect with, and empathize with others is especially pronounced in this phase. This study aimed to develop and validate a self-report empathy measure for adolescents, the Multidimensional Empathy Scale for Adolescents (MESA). Based on the theories and research on empathy, we created 24 items to measure six dimensions of empathy (cognitive, affective, positive, negative, majority, and minority). The dimensional structure of the MESA was examined in two independent samples of adolescents. The hypothesized six-factor model of the MESA showed a good fit for both samples. Reliability analyses demonstrated that the MESA had high internal consistency and test–retest reliability. Furthermore, the MESA showed high convergent, discriminant, and incremental validity, as indicated by positive correlations with existing measures of empathy, idiocentrism–allocentrism, and social interest scales. The MESA, as a unique measure of six types of empathy, can be a valuable tool to assist adolescents in developing a balanced sense of empathy.
Keywords: adolescents; empathy; self-report assessment; validity